2013
DOI: 10.1177/0972262912483529
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Organizational Commitment Relationship: Effect of Personality Variables

Abstract: The purpose of the study was to explore the relationship between Job Satisfaction and Organizational Commitment and to investigate the moderating effects of Trust and Locus of Control on the relationship between Job Satisfaction and Organizational Commitment. The study was administered on 247 middle level managers belonging to private sector organizations. Four validated instruments were used in the study. Statistical tools like Descriptive Statistics, Factor Analysis, Pearson Product Moment Correlation and Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 42 publications
8
53
0
8
Order By: Relevance
“…Also, the study found a statistically significant impact of tangibles, reliability, responsiveness, assurance and empathy on patient satisfaction. [14], using a sample of 247 middle-level managers in the banks, and the IT sectors, found that job satisfaction is positively related to organizational commitment. He also found that managers with internal locus of control are more satisfied with their jobs and hence they are more committed towards their organizations.…”
Section: Job Satisfaction and Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study found a statistically significant impact of tangibles, reliability, responsiveness, assurance and empathy on patient satisfaction. [14], using a sample of 247 middle-level managers in the banks, and the IT sectors, found that job satisfaction is positively related to organizational commitment. He also found that managers with internal locus of control are more satisfied with their jobs and hence they are more committed towards their organizations.…”
Section: Job Satisfaction and Organizational Commitmentmentioning
confidence: 99%
“…An example of such methods includes the ability of organizations to adopt positive organizational attitudes such as job involvement and job satisfaction [12]. Furthermore, having a motivated, involved, and committed workforce is considered an important asset to an organization's success as keeping employee motivation, commitment and job involvement up leads to improved productivity and lower turnover rates [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à força do coeficiente de correlação, observou que é moderada, já que ficou entre 0,31 e 0,59 (APPOLINÁRIO, 2006). Visto que o comprometimento afetivo é um dos tipos de comprometimento, conforme a teoria de Allen e Meyer (1990), esses resultados corroboram as pesquisas que apontam existir níveis de correlação positiva entre a satisfação e o comprometimento afetivo (COSTA;BASTOS, 2009;TRALDI;DEMO, 2012;PATRICK;SONIA, 2012;SRIVASTAVA, 2013).…”
Section: Análise Dos Resultadosunclassified
“…Also, the relationship between loneliness, job satisfaction, and organizational commitment of migrant workers in China, controlling for age, gender, and marital status was examined by Chan and Qiu (2011).  Other Factors Impacting Job Satisfaction include: bonus intensity (Pouliakas, 2010), individual and gain-sharing incentives (Pouliakas and Theodossiou, 2009), equity sensitivity (Ahmad, 2011), equal opportunity climate (Walsh et al 2010), ethical climate (Wang and Hsieh, 2012), perceived managerial support (Sawang, 2010), organizational context (Parzinger et al 2012), previous job perception (Badillo Amador et al 2012); occupational position (Kawada and Otsuka, 2011); years of tenure (Boswell et al 2009), stress (Kawada and Otsuka, 2011;Singh and Ashish, 2011;Anton, 2009), locus of control (Singh and Ashish, 2011), personal and organizational values (Kumar, 2012), personality variables (Srivastava, 2013), interaction of individual and structural temporalities (Agypt and Rubin, 2012), engagement (Alarcon and Lyons, 2011), emotional intelligence (Jorfi et al 2012;Narayanan and Zafar, 2011), balanced scorecard characteristics (Burney and Swanson, 2010), job characteristics (Morris and Venkatesh, 2010); job complexity and autonomy (Chung-Yan, 2010), and even gender (Grissom et al 2012) and serotonin genes (Song et al 2011). Researchers study both mediating and moderating roles of job satisfaction.…”
mentioning
confidence: 99%
“…For instance: various aspects of job satisfaction in health-care organizations and factors contributing to a relatively low level of job satisfaction of medical teachers (Bhatnagar and Srivastava, 2012;2013); factors affecting employees' job satisfaction in public hospitals (Miryala and Thangella, 2012;2013 andRad andDe Moraes, 2009); factors influencing job satisfaction amongst doctors in corporate and private hospitals (Miryala and Thangella, 2012;2013); relationships among internal marketing perceptions, organizational support, job satisfaction and role behavior in healthcare organizations (Yang, 2010), determinants of job satisfaction and intentions to quit of offshore workers in the UK North Sea oil and gas industry (Dickey et al 2011), job satisfaction of university teachers (Sharma and Jyoti, 2009); job satisfaction of municipal clerks (Gordon et al 2010); job satisfaction of knowledge workers (Bakotic, 2012); role of stress and locus of control in job satisfaction among middle managers (Singh and Ashish, 2011); organizational learning capability and job satisfaction in the ceramic tile industry (Chiva and Alegre, 2009); relationship between college quality, earnings, and job satisfaction among recent college graduates (Liu et al 2010); ministry clergy burnout and job satisfaction (Miner et al 2010); job satisfaction in the public service (Taylor and Westover, 2011); relationships among transformational leadership, job satisfaction, commitment foci and commitment bases in the public sector (Yang et al 2011b, p.265-278); impact of management reform on employee job satisfaction in federal agencies (Yang and Kassekert, 2010); job satisfaction in the home health care context (Morgan et al 2010); and even individual and environmental factors related to job satisfaction in people with severe mental illness employed in social enterprises (Villotti, 2012).…”
mentioning
confidence: 99%